Pathways towards women empowerment and determinants of decent work deficit: A South Asian perspective - Mudassira Sarfraz; Zubaria Andlib; Muhammad Kamran; Noor Ullah Khan; Hanieh Alipour Bazkiaei (Administrative Sciences, 2021)
This research aims to assess the household and individual-level factors, specifically education, that affect the probability of women being engaged in decent work activities in the labor market. The study utilized the most recent labor force survey data from Pakistan with a sample size of 64,009 women. The research exploits the multinomial logit model (MNL) for data analysis. Several studies exist on the causes of female labor force participation nationally - in Pakistan - and internationally. However, there is a lack of research exploring the link between women's access to decent work and various household and individual-level characteristics. This study intends to fill this literature gap by exploiting the largest nationwide labor force survey and exploring how household and individual-level factors, specifically focusing on women's education level, relate to women's employment status categories. The study's findings reveal that education plays an essential role in uplifting women for better employment opportunities, i.e., educated women are more likely to be engaged in decent labor market activities such as paid employees and employers. The findings of the study propose some significant policy implications. E.g., (i) since education is the key to open better and decent work opportunities, it is crucial for women and their household heads to invest in education and vocational training; (ii) there is a dire need to have a policy shift in providing women access to at least a higher secondary (HS) level of education in Pakistan. The rationale is that less educated and illiterate women are concentrated in vulnerable employment; and (iii) at a micro level, there is a need to bring awareness among male household heads, specifically in rural areas, to realize that working women should not be considered a social stigma for the household.
Keywords: 350; decent work deficit; education; South Asia; women's employment status